ChemInform Abstract: Silver Triflate‐Catalyzed Tandem Reaction of N′‐(2‐Alkynylbenzylidene)hydrazide with Pyridyne. Issue 14 (20th March 2013) - Jiang, Lingyong; Yu, Xingxin; Fang, Bing; Wu, Jie
Abstract The reaction of (alkynylbenzylidene)hydrazines (I), bearing either alkyl or phenyl substituents on the triple bond, with pyridine derivative (II) works well to produce the pyridine‐fused pyrazoloisoquinolines in good yields, although the transformations occur not regioselectively.